Analysis of deep crack formation and propagation in railway brake discs. (October 2021) - Xie, Xiaodong; Li, Zhiqiang; Domblesky, Joseph P.; Yang, Zhiyong; Liu, Xiaolong; Li, Weijing; Han, Jianmin
Graphical abstract: Highlights: A steel brake disc was analyzed after a deep crack was discovered. Finite element and extended finite element models were used in the simulation. Service induced distortion could have a strong effect on crack behavior. The transient temperature differences help to define the crack behavior. Abstract: While surface crack formation and propagation in Electric Multiple Unit (EMU) brake discs has been an active research topic, relatively few studies have considered similar behavior in deep cracks which become unstable. Moreover, most analyses assume nominal design conditions which does not reflect changes which may have been occurred during service. In the present study, a steel brake disc was analyzed after a deep crack was discovered during a maintenance check. The objective was to identify the impetus for deep crack propagation and characteristic semi-elliptical shape. Finite element (FEM) and extended finite element (XFEM) models which included residual stress effects from service were used to analyze the thermo-mechanical history and resulting crack propagation. The simulated and actual fracture surfaces demonstrated satisfactory agreement and showed that the crack preferentially initiated at the bolt hole corners and that transient temperature differences between adjacent hot spots help to define the crack orientation. It was also found that unstable propagation along the axial direction was due to a steep temperature gradient. Service induced distortion was also found to indicate the presence of internal stresses which can have a strong effect on crack behavior. It is expected that the findings will contribute toward a better understanding of how braking conditions and service effects influence unstable crack behavior in EMU brake discs.